Brackish Water Shrimp Farming and the Growth of Aquatic Monocultures in Coastal Bangladesh - Pokrant, Bob (Springer Netherlands, 2014)
One of the most significant changes in marine and coastal environments since the mid–twentieth century has been the growth of coastal shrimp aquaculture in many tropical and sub–tropical regions of the world. This chapter, which draws on the author’s own archival and field research and the published works of other students of the global shrimp market, examines the growth of brackish water shrimp production from the 1970s to the present in Bangladesh’s coastal belt and its social and ecological impacts. It shows that for most of this period shrimp production was encouraged by the Bangladesh Government to expand in a fragmented and uncoordinated way with varying environmental, economic and social consequences. These included higher levels of soil salinity, increased risk of flooding, loss of agricultural land, a decline in biodiversity, contraction of various traditional occupational activities, growth in new non-agricultural work, a shift to diversified employment strategies among households, higher incomes for shrimp farmers and land renters and economic and social dislocation for others. Government, business and international aid agencies supported the expansion of mono–cultural forms of shrimp production integrated into global trading networks at the expense of local resource extraction activities such as artisanal fishing and forestry.